Orbitocranial Approaches to the Skull Base - Vincent, Aurora; Wang, Weitao; Sokoya, Mofiyinfolu; Kadakia, Sameep; Chan, David; Ducic, Yadranko (Seminars in Plastic Surgery, 2019)
There are a myriad of approaches and surgical options for removal and treatment of skull base diseases. While, historically, large open approaches have been preferred, several endoscopic and minimally invasive techniques are now available that preserve intraoperative visualization and surgical success while minimizing morbidity and recovery times. Herein, the authors review common open, minimally invasive, and endoscopic approaches to the anterior skull base.
Keywords: anterior skull base; orbitocranial approaches; transfacial; transbasal